Phenolics, fibre and fibre digestibility in the crop residue from bird resistant and non-bird resistant sorghum varieties - Reed, J.D.; Tedla, A.; Kebede, Y. (Wiley, 1987)
A study conducted to determine the difference between BR and NBR varieties in content of phenolics and their relationship to digestibility of fibre in the crop residue.